Pemanfaatan Limbah Plastik Polyethylene Terephthalate (PET) Sebagai Agregat Kasar Beton Ringan: Systematic Literature Review - Arrisha Anggraini; Wenny Herdianti; Ivana Christine Sembiring Brahmana; Titonik Feberman Hia; Melvi Maulita Napitupulu; I Gede Wyana Lokantara (JURNAL TECNOSCIENZA, 2026)
Plastic waste, particularly polyethylene terephthalate (PET) from beverage bottles, constitutes a major source of non-biodegradable waste that is difficult to decompose and poses long-term environmental risks. The utilization of polyethylene terephthalate (PET) waste as a partial replacement for coarse aggregate in concrete offers a dual benefit: reducing plastic waste while conserving natural aggregates and decreasing concrete density for lightweight applications.This study systematically examines the mechanical properties of polyethylene terephthalate (PET)-based concrete through a systematic literature review following the PRISMA 2020 protocol, covering publications from 2018 to 2026. A literature search was conducted across the SINTA, Portal Garuda, Google Scholar, and Scopus databases, yielding 155 initial articles. After a rigorous screening process, 7 experimental studies met the inclusion criteria, namely those that utilized polyethylene terephthalate (PET) as a coarse aggregate substitute and reported quantitative data on compressive strength and/or density. The synthesis reveals a consistent trend in which increasing polyethylene terephthalate (PET) content reduces compressive  strength (ranging from 13–20 MPa at 5–10% substitution and 7–10 MPa at >25%) as well as density (1,645–1,900 kg/m³), resulting in lightweight non-structural concrete. A combination of PET and rice husk ash achieved an optimal compressive strength of 24.85 MPa. Substitution levels of 5–10% are most suitable for semi-structural elements, whereas levels above 25% are optimal for non-structural applications such as partition panels and precast drainage channels.